2015
DOI: 10.5588/ijtld.14.0939
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of chronic obstructive pulmonary disease in Riyadh, Saudi Arabia: a BOLD study

Abstract: The overall prevalence of COPD in Saudi Arabia is 4.2%. Male, increasing age and smoking were the main risk factors for COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
2
15
1
Order By: Relevance
“…The first study ever in the region was that of Al Zaabi et al in 2011, and results were comparable to the largest questionnaire-based BREATHE study in the MENA region. 21 , 22 Three studies were based on the BOLD protocol: Al Ghobain et al in Saudi Arabia, 25 Daldoul et al in Tunisia, 30 and El Rhazi et al in Morocco. 31 The other studies have already been described herein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first study ever in the region was that of Al Zaabi et al in 2011, and results were comparable to the largest questionnaire-based BREATHE study in the MENA region. 21 , 22 Three studies were based on the BOLD protocol: Al Ghobain et al in Saudi Arabia, 25 Daldoul et al in Tunisia, 30 and El Rhazi et al in Morocco. 31 The other studies have already been described herein.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated sex- and age-based prevalence of COPD also showed varied results. All studies reviewed demonstrated either statistically significant increased prevalence in males over females 21 , 25 , 29 or no difference. 22 , 23 , 28 This inconsistency can be explained by the wide variation in smoking prevalence in females within the region, differences in cultural background, and differences in exposure to other risk factors, eg, biomass fuel.…”
Section: Incidence and Prevalence Of Copd In Gcc–mena Regionmentioning
confidence: 95%
See 2 more Smart Citations
“…Another survey using the European Community Respiratory Health Survey questionnaire carried out in Riyadh among a total of 2405 Saudi people aged between 20-44 years showed that the prevalence of physician-diagnosed asthma reported was 11.3% [20]. Regarding COPD, the overall prevalence of COPD in Saudi Arabia is 4.2% [21].…”
Section: Resultsmentioning
confidence: 99%